2019
DOI: 10.1128/jb.00273-19
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Whole Fusobacterium Genomes To Identify, Correct, and Characterize Potential Virulence Protein Families

Abstract: Fusobacterium spp. are Gram-negative, anaerobic, opportunistic pathogens involved in multiple diseases, including a link between the oral pathogen Fusobacterium nucleatum and the progression and severity of colorectal cancer. The identification and characterization of virulence factors in the genus Fusobacterium has been greatly hindered by a lack of properly assembled and annotated genomes. Using newly completed genomes from nine strains and seven species of Fusobacterium, we report the identification and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 86 publications
1
54
0
Order By: Relevance
“…While FadA has been shown to drive interactions with cancer cells, we note that these studies were done in the strain F. nucleatum 12230 ( 31 , 37 , 38 ). Upon bioinformatic analysis, we found that F. nucleatum 23726 contains four fadA ortholog genes ( fadA2, fadA3a, fadA3b, fadA3c ), and F. nucleatum 12230 encodes for only one orthologue ( 23 ). This could mean that a single deletion of the fadA gene in F. nucleatum 23726 remains adhesive, and that multiple fadA family proteins are contributing to binding and invasion.…”
Section: F Nucleatum 23726 Outer Membrane Adhesins Are Critical For mentioning
confidence: 98%
See 1 more Smart Citation
“…While FadA has been shown to drive interactions with cancer cells, we note that these studies were done in the strain F. nucleatum 12230 ( 31 , 37 , 38 ). Upon bioinformatic analysis, we found that F. nucleatum 23726 contains four fadA ortholog genes ( fadA2, fadA3a, fadA3b, fadA3c ), and F. nucleatum 12230 encodes for only one orthologue ( 23 ). This could mean that a single deletion of the fadA gene in F. nucleatum 23726 remains adhesive, and that multiple fadA family proteins are contributing to binding and invasion.…”
Section: F Nucleatum 23726 Outer Membrane Adhesins Are Critical For mentioning
confidence: 98%
“…We recently bioinformatically identified five Type 5c adhesins in the strain F. nucleatum 23726, with four of these (CbpF, FvcB, FvcC, FvcD) containing all of the classic domains that make up a complete adhesin. The fifth protein (FvcE, not characterized) lacks a 'head' domain that is predicted to coordinate adhesion ( 23 ). To study these proteins, we made the first complete, single gene knockouts of these six adhesin genes ( fadA, fap2, cbpF, fvcB, fvcC, fvcD) in F. nucleatum 23726, as well as multiple gene deletions per strain ( Table S1-3 ) using a new version of a galactose kinase (GalK) genetic system previously used in F. nucleatum ( 35 ), as well as many classical studies in Clostridium ( 36 ).…”
Section: F Nucleatum 23726 Outer Membrane Adhesins Are Critical For mentioning
confidence: 99%
“…The genes encoded by homologs of FN1529 and FN1528 were previously unnamed and will be referred to in this study as rapA (radD-associated proteins A) and rapB, respectively. Based on the sequence similarity of RapA to the previously characterized FadA adhesin [18], rapA was also suggested to be named fadA2 by a very recent bioinformatic study [23]. All the four genes of the operon are predicted to be associated with membrane with Predict Protein (www.predictprotein.com accessed on 10 October 2019).…”
Section: Resultsmentioning
confidence: 99%
“…No function has been identified for the two other proteins encoded by the additional genes in the operon, which we denominated as RapA and RapB (RadD-associated proteins). While a recent study highlights the similarity of RapA to the fusobacterial adhesin FadA and suggests it to be FadA2, functional characterization is still missing [23].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the findings from previous reports 59,60 , Epulopiscium was significantly enriched in the CDI group and played an important role in differentiating this comparison. Among those features selected from the classification of CDI and Non-CDI groups, Enterobacter and Fusobacterium have been considered as opportunistic pathogens involved in multiple diseases 61,62 .…”
Section: Discussionmentioning
confidence: 99%